Iron Deficiency Anaemia with Underlying Beta-Thalassaemia Carrier in a Single Mother with Multiple Substance Abuse: A Case Report - Idris, Mohd Faznynell; Rashid, Aneesa Abdul (International Journal of Human and Health Sciences (IJHHS), 2025)
Anaemia in pregnancy is a common condition in primary care, and severe cases require prompt intervention. We report a 23-year-old single mother with a history of smoking and substance abuse who was diagnosed with severe iron deficiency anaemia in late pregnancy and later developed postpartum haemorrhage. Although asymptomatic, she required admission, blood transfusions, and parenteral iron. Her substance use complicated her management. Further tests confirmed a beta-thalassaemia trait, prompting family screening. This case highlights the importance of a multidisciplinary approach in high-risk pregnancies. International Journal of Human and Health Sciences Vol. 09 No. 03 Jul’25 Page: 191-193